Religiusitas, Empati dan Perilaku Prososial Jemaat GKT Hosana Bumi Permai - Juliwati, Juliwati; Suharnan, Suharnan (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2014)
Abstract. Prosocial behavior is a form of behavior that emerge in social contacts, so that prosocial behavior is an action taken or planned to help others , caring about the motives of the helper . Helping action is fully motivated by their own interests without expecting anything. Prosocial action is more demanding on the high sacrifice of the doer and voluntary or shown to benefit others rather than getting material or social rewards. Prosocial behavior is influenced by many variables , in this study , the researcher linking prosocial behavior with religiosity and empathy . This study aims to determine whether there is a correlation between prosocial behavior with religiosity and empathy. The results of this study are expected to provide information for Assembly GKT Hosana Bumi Permai to develop prosocial behavior congregation. Having receached to 64 people of GKT Hosana Bumi Permai shows that together religiosity variables and empathy has a significant corelation with prosocial variables. Religiosity variables have no correlation with Prosocial , whereas empathy variables have significant association with Prosocial variablesKeywords : prosocial behavior, religiosity, empathyÂ